SEISMIC ATTRIBUTE ANALYSIS FOR HYDROCARBON PROSPECTING IN THE AGBADA FORMATION OF 'ZEE' FIELD, NIGER DELTA BASIN - Allo, Olawale Johnson; Ogundimu, Toba Sheriffdeen (FUDMA JOURNAL OF SCIENCES, 2024)
The unconsolidated sandstone reservoirs of the Tertiary Nigeria Delta basin are prone to anomalous high amplitude seismic reflections from both hydrocarbon and non-hydrocarbon sources. In order to identify anomalous zone due to hydrocarbon presence, seismic attribute analysis was used to investigate the reservoirs and to detect Direct Hydrocarbon Indicators (DHIs) due to hydrocarbon saturation in the ‘Zee’ field reservoirs. The 3D seismic, well logs and checkshot data were used for structural interpretation which helped to identify the sandstone and hydrocarbon bearing reservoirs. Faults planes and horizon were mapped to highlight the structural geometry and reservoir surface detection respectively. Five different seismic attributes were used to qualitatively evaluate hydrocarbon prospect from seismic amplitudes. Seismic attributes revealed three (3) major normal growth faults across the field while two (2) reservoirs (shallow seated reservoir A and deep reservoir B) showed zones that contain hydrocarbon anomalies. Seismic amplitude responses and fault styles from the reservoir tops reveal structurally controlled fault dependent closure across the field. High seismic amplitude anomalies from RMS, Average Energy and Maximum Magnitude attributes significantly characterize the drilled parts of the field. This implies that the high amplitude anomaly is a DHIs in ‘Zee’ Field. Moreover, apart from the already producing zone in the field's central area, two (2) more areas marked X and Y situated on anticlinal structure at the North East corner of the field has similar high amplitude responses (bright spots). It suggests new hydrocarbon prospects that should further be investigated for more hydrocarbon discoveries.
Keywords: 3D-Seismic; Attributes; Hydrocarbon; Prospects; RMS; Closure